Review of the studies on emission evaluation approaches for operating vehicles - Pu Lyu; Peirong (Slade) Wang; Yuanyuan Liu; Yuanqing Wang (Journal of Traffic and Transportation Engineering (English ed. Online), 2021)
With the increasing international consensus concerning the negative effects of climate change, reducing greenhouse gases has become a higher priority in government policies and research committees. The transportation sector generates approximately 29% of the total greenhouse gas emissions and 25% of the global energy related carbon dioxide (CO2) emissions. Thus, it is essential to understand the influencing factors of vehicle emissions and establish a corresponding evaluation model for the emission estimation of operating vehicles. This paper reviews different methods of measuring vehicle emissions, including laboratory measurements, on-road measurements, and tunnel measurements. Then, we summarize the factors affecting the emission evaluation of operating vehicles based on the vehicle operating features and road environment. Finally, the applications of vehicle emission evaluation models are analyzed, including the emission assessment of the vehicles operating at road segments and intersections. Based on this review, one can conclude that selecting different measurements will significantly impact the assessment of the vehicle emission results and the applicable scope of the measurements. Considering the different influencing factors of the operating vehicle emissions will have an impact on the model application of the vehicle emission evaluation. Moreover, several analysis methods for new technology vehicles can compensate for the potential lack in connectedness with the rapid development of new energy vehicle technology and the improvement of intelligent transportation systems (ITS).